Ammonia oxidation capacity of bacillus bacteria in swine wastewater after biogas treatment - Huu Dong Nguyen; Thi Viet Nguyen; Thi Thu Hang Dinh; Do Hung Phan Do; Hoa Duan Tran (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên, 2022)
Nitrogen removal with biological methods plays a crucial role in wastewater treatment technology. The treatment begins with the oxidation of ammonia to nitrite to facilitate the subsequent nitrification and denitrification. Various strains of ammonia-oxidising bacteria have been reported. In this study, we use three Bacillus bacteria isolated from swine wastewater to oxidise ammonia. Different initial densities (103, 104, 105, and 106 CFU·mL–1) of each strain were examined. The results show that the combination of all the bacteria at a ratio of 1:1:1 and a density of 105 CFU·mL–1 exhibits the most effect. The findings contribute to the diversity of ammonia-oxidising bacterial species and pose a great potential for applying these strains in wastewater treatment.